Upaya Meningkatkan Kreativitas Siswa Dalam Pembelajaran Biologi Melalui Penerapan Model Pembelajaran Kooperatif Type Jigsaw di SMA Negeri 2 Balige - Pasno Lingga (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This classroom action research is executed in class XI IA2 Semester 2 of SMA Negeri 2 Balige academic year 2011/2012, aim to know whether model  of co-operative of leraning Jigsaw type can improve student creativity in course study of Biology at System Hormone and Indra. Research of method is taken by writing down dominant perception category emerge during take place at perception sheet ( Instrument). In intake of data, researcher presents directly of study items as many as 4 cycle. Every cycle  consists  of  four  phrases.  They are  planning,  action,  observation,  and Reflection. Every cycle assisted by 2 people as observer to collect uppermost student creativity data at the same time give suggestion / inputs repair of study process. Cycle of I by applying conventional method (discussion and discourse) while cycle of II, III, and IV by applying model of co-operative of learning Jigsaw type. From result of observation and perception analyse data obtained by conclusion that model of co-operative of learning Jigsaw type can improve class student creativity of XI IA2 SMA Negeri  2 Balige in course study of Biology hormone system and Indra of student creativity mean 59,80 at conventional study become 77,13 (the first group) and 85 % ( expert team), second cycle, 83,24 (the first group) and 92,95% ( expert team), third cycle and 85,09 ( the first) and 95,45 % (expert team) at fourth cycle by applying model study of jigsaw. The result of examination with using convensional method only 8 students, but using model of cooperative of learning jigsaw type, the student can be able more b competence and improving to be 22 student. The conclution of the study shows that implementation cooperative of learning jigsaw type accompany with modul about contamination and enviromental change can improve student learning activity in class XI IA2 at SMA Negeri 2 Balige in academic year 2011/2012. Keywords: Cooperative Learning model, Jigsaw, creativity student